Nanotube film based on single-wall carbon nanotubes for strain sensing - Dharap, P.; Li, Z.; Nagarajaiah, S.; Barrera, E.V.
strains. In this study, the strain sensing characteristic of carbon nanotubes is used to develop a carbon nanotube film sensor that can be used for strain sensing on the macro scale. The carbon nanotube film is isotropic due to randomly oriented bundles of single-wall carbon nanotubes (SWCNTs). Using experimental results it is shown that there is a nearly linear change in voltage across the film when it is subjected to tensile and compressive stresses. The change in voltage is measured by a movable four-point probe in contact with the film. Multidirectional and multiple location strains can be measured by the isotropic carbon nanotube film.